Effects of Regional Transport on Haze in the North China Plain: Transport of Precursors or Secondary Inorganic Aerosols - Huiyun Du; Jie Li; Zifa Wang; Xu Dao; Song Guo; Lingling Wang; Shuangliang Ma; Jianbin Wu; Wenyi Yang; Xueshun Chen; Yele Sun (Geophysical Research Letters)
Abstract Most previous studies treat regional transport of aerosols as a whole, without distinguishing the transport of secondary aerosols and that of their precursors. A new method of quantifying the transport forms of secondary inorganic aerosols (SIA) using the Nested Air Quality Prediction Modeling System was proposed. The contribution of nonlocal emissions to SIA in the receptor region was divided into three parts: (1) SIA chemically formed by nonlocal emissions in their source regions; (2) SIA chemically formed by nonlocal emissions during transport; and (3) SIA chemically formed by nonlocal emissions in the receptor region, representing transport of precursors. In the North China Plain, the transport of precursors and SIA produced during transport are the two main transport forms. Furthermore, the contribution from transport of precursors increased under polluted conditions in most cities. The results indicate that joint control of precursors is paramount for mitigating air pollution.